IFC Jobs Study : Assessing Private Sector Contributions to Job Creation and Poverty Reduction - International Finance Corporation (World Bank, Washington, DC, 2014)
This report is the result of an open-source study to assess the direct and indirect effects of private sector activity on job creation. The report examines how and under what conditions the private sector can best contribute to job creation and poverty reduction. The private sector, which provides some 90 percent of jobs in developing countries, must be at the core of any response to this double challenge. Therefore, it is crucial to understand the constraints that private companies face in creating jobs, and the public sector and development finance institutions must help build an environment where these obstacles are removed or minimized. This report aims to help by providing an understanding of how the private sector generates jobs, what constraints limit job creation, and how these problems can be mitigated. The world is thus facing a double jobs challenge: creating a large number of jobs and creating better jobs. The economic crisis has added 27 million new unemployed; leading to a total of 200 million unemployed worldwide in 2011. More than 600 million jobs must be created in the next decade to ensure that unemployment does not increase even further as millions of young people enter the workforce. Private sector job cre-ation is inextricably linked to overall development and poverty reduction, making it crucial to understand how the private sector creates jobs, what obstacles limit job creation, and how those obstacles can be mitigated. This is precisely the supporting role of the public sector: provide the necessary macroeconomic environment and a supportive investment climate. Development finance institutions can support the public sector in that process, in addition to working directly with private companies. Development cannot take place without jobs. Therefore, the world needs to act now to address the enormous jobs challenge that confronts it. The main message for policymakers is that job creation, socioeconomic development, and poverty reduction are not independent, and thus policies aimed at these should be designed and implemented in an integrated manner. In particular, job policies should be a central part of any development policy, and they should tackle the double-sided challenge of generating more jobs and better jobs. The second message is that because the private sector is the main engine of growth and job creation, it is fundamental to understand both what drives job creation and what obstacles prevent the private sector from generating jobs. This report aims to understand the effects of constraints and of policies removing them on job creation, while identifying the circumstances under which these policies are likely to work. The report also contains some estimates of the magnitude of the employment-generation effects.